2014
DOI: 10.1371/journal.pone.0097420
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Induced Depression during a Frustrating Situation: Benefits of Expressive Suppression in Chinese Individuals

Abstract: BackgroundStudies from European-American cultures consistently reported that expressive suppression was associated with worse emotional consequence (e.g. depression) in comparison with acceptance. However, this conclusion may not apply to Chinese, as suppressing emotional displays to maintain relational harmony is culturally valued in East Asian countries. Thus, the present study examined the effects of suppression and acceptance on the depressive mood induced by a frustrating task in a Chinese sample.MethodSi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 77 publications
5
22
0
Order By: Relevance
“…The moderating effect of trial duration on suppression and skin conductance level was mainly driven by one study (Yuan et al, 2014).…”
Section: Trial Durationmentioning
confidence: 99%
“…The moderating effect of trial duration on suppression and skin conductance level was mainly driven by one study (Yuan et al, 2014).…”
Section: Trial Durationmentioning
confidence: 99%
“…Expressive suppression is a widely used emotion regulation strategy, and this strategy has been proved particularly effective in regulating emotional consequences in East Asian societies ( Butler et al, 2007 ; Yuan et al, 2014a , b ). The suppression of inappropriate emotion-expressive behaviors, especially unpleasant ones, plays an important role in humans’ social adaptation and the maintenance of relational harmony ( Kitayama et al, 2000 ; Mesquita, 2001 ; Murata et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another possible explanation is the cultural differences of emotion regulation. The current study used a Chinese sample and it has been found in previous literature that suppression is adaptive in Chinese culture, as indexed by larger declines in physiological response including skin-conductance and late positive potentials (Yuan et al, 2014a , b ). We are not sure about which of the aforementioned accounts is the correct explanation for smog-induced psychopathology and it seems like an important future direction for research on air pollution and psychopathology as well as effectiveness of emotion regulation strategies.…”
Section: Discussionmentioning
confidence: 99%